2004
DOI: 10.1038/sj.bjc.6602256
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ER, PgR, HER-2 and Ki-67 as predictors of response to neoadjuvant anthracycline chemotherapy for operable breast cancer

Abstract: Primary systemic therapy (PST) for operable breast cancer enables the identification of in vivo biological markers that predict response to treatment. A total of 118 patients with T2 -4 N0 -1 M0 primary breast cancer received six cycles of anthracycline-based PST. Clinical and radiological response was assessed before and after treatment using UICC criteria. A grading system to score pathological response was devised. Diagnostic biopsies and postchemotherapy surgical specimens were stained for oestrogen (ER) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
116
1
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(137 citation statements)
references
References 65 publications
(71 reference statements)
13
116
1
5
Order By: Relevance
“…The overall frequency of patients with HR status conversion was 16.0%. This incidence of HR status conversion was similar to previous reports on post-NAC change in the ER, PgR, and HER2 statuses, which reported incidences of 8 -28%, 6 -59% (Bottini et al, 1996;Lee et al, 2003;Taucher et al, 2003;Colleoni et al, 2004;Burcombe et al, 2005;Shet et al, 2007;Kasami et al, 2008;Neubauer et al, 2008), and 0 -21% (Bottini et al, 1996;Colleoni et al, 2004;Arens et al, 2005;Burcombe et al, 2005;Quddus et al, 2005;Adams et al, 2008;Kasami et al, 2008;Neubauer et al, 2008), respectively. Although the rate of cases with no change in the HR status after NAC was high, the incidence of change in the HR status is clinically not negligible.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The overall frequency of patients with HR status conversion was 16.0%. This incidence of HR status conversion was similar to previous reports on post-NAC change in the ER, PgR, and HER2 statuses, which reported incidences of 8 -28%, 6 -59% (Bottini et al, 1996;Lee et al, 2003;Taucher et al, 2003;Colleoni et al, 2004;Burcombe et al, 2005;Shet et al, 2007;Kasami et al, 2008;Neubauer et al, 2008), and 0 -21% (Bottini et al, 1996;Colleoni et al, 2004;Arens et al, 2005;Burcombe et al, 2005;Quddus et al, 2005;Adams et al, 2008;Kasami et al, 2008;Neubauer et al, 2008), respectively. Although the rate of cases with no change in the HR status after NAC was high, the incidence of change in the HR status is clinically not negligible.…”
Section: Discussionsupporting
confidence: 90%
“…The hormone receptor (HR) status is one such factor. Although this status is known to change after NAC (Bottini et al, 1996;Lee et al, 2003;Taucher et al, 2003;Colleoni et al, 2004;Burcombe et al, 2005;Shet et al, 2007;Tacca et al, 2007;Kasami et al, 2008;Neubauer et al, 2008), its impact on long-term outcomes has not been assessed. The objective of this retrospective study was to evaluate the frequency and impact of change in the HR status (HR status conversion) on the long-term outcomes in the NAC-administered breast cancer patients.…”
mentioning
confidence: 99%
“…after neoadjuvant chemotherapy was reported in several studies (112)(113)(114). In general, studies that reported a good concordance of hormone receptor status before and after neoadjuvant chemotherapy had a relatively smaller number of patients compared to the studies that found significant changes.…”
Section: Serial Changes In Expression Of Proteins In Response To Neoamentioning
confidence: 79%
“…Several research groups observed significant changes in expression levels of tumour parameters like ER·, PR or Her-2 during PST (15)(16)(17)(18)(19)(20)(21)(22)(23). Therefore, it is strongly recommended that hormone receptor expression and other biological markers should be re-evaluated after PST in order to make sure that post-surgery treatment is tailored adequately.…”
Section: Introductionmentioning
confidence: 99%